Glucagon-like peptide-1 inhibits gastric emptying via vagal afferent-mediated central mechanisms - (:unkn) unknown (AMER PHYSIOLOGICAL SOC, 1997)
Exogenous administration of glucagon-like peptide-1-(7-36) amide (GLP-1), an insulinotropic hormone, inhibits gastric emptying and acid secretion in humans. The role of GLP-1 as a regulator of gastric function is elusive. In gastric fistula rats, vagal afferent denervation and peripheral administration of the GLP-1 receptor antagonist exendin-(9-39) amide enhanced emptying of a glucose meal, whereas intracerebroventricular exendin was ineffective. The rate of saline emptying was attenuated by peripheral as well as by central administration of GLP-1, and pretreatment with exendin by the respective routes reversed the inhibition by GLP-1. Vagal afferent denervation abolished the central and peripheral action of GLP-1 on gastric emptying. Neither peripheral cholinergic nor adrenergic blockade altered the delay of methyl cellulose meal emptying by intracisternal GLP-1 injection. Acid secretion in conscious pylorus-ligated rats was inhibited by intracisternal GLP-1 administration, whereas systemic GLP-1 was ineffective. These results support the notion that GLP-1 receptors participate in the central and peripheral regulation of gastric function. Furthermore, vagal afferent nerves mediate the inhibitory action of GLP-1 on gastric motor function. GLP-1 may be a candidate brain-gut peptide that acts as a physiological modulator of gastric function.
Keywords: acid secretion; glucose; feeding behavior; exendin; ACID-SECRETION; RAT-BRAIN; TRUNCATED GLP-1; PROGLUCAGON; ANTAGONIST; RECEPTOR; AMIDE; EXENDIN-4; INCRETIN; LOCALIZATION